MEASURING ERROR MANAGEMENT CULTURE: SCALE DEVELOPMENT AND VALIDATION - Nanto, Zülküf; Özan, Mukadder Boydak (My University, 2022)
In this study, the error management culture scale (EMC-S) was developed. The sample of the research consistsof636 teachers in the city center of Elazığ. Lawshe technique was used by taking expert opinions to ensure the scope and face validity and exploratory and confirmatory factor analyzes were performed to ensure construct validity. In the first stage, a draft version of the scale was developed by employing the Lawshe technique. In the second stage, exploratory factor analysis (EFA) was performed with the participation of three hundred twelve teachers. Before the analysis, the data was screened to determine whether the data were appropriate for factor analysis. The results of the EFA confirmed that the scale has sixteen items with four factors. The factors were entitled as error sharing (five items), error competence (five items), error avoidance (three items), and response to error (three items). In the third stage, confirmatory factor analysis (CFA) was conducted with three hundred twenty four different participants. The results revealed proof of recommended agreement (CFI=.945, NFI=.958, GFI=.927, SRMR=.051, RMSEA=.058). In addition, reliability of the scale was calculated. The reliability coefficient values for factors and the scale was over .782, which proved that the scale is highly reliable.
Keywords: Scale Development; Scale Validation; Error Management Culture